Causal Inference in Spatial Mapping. Issue 10 (October 2019) - Kraemer, Moritz U.G.; Reiner, Robert C.; Bhatt, Samir
Abstract : Disease mapping has evolved to a powerful field in epidemiology and public health to focus interventions. Increased precision has come at the expense of interpretability. We propose that future efforts should focus on causal inference to evaluate and predict the effectiveness of intervention strategies to guide decisions more effectively.